Memory, history, and autobiography in early modern towns in east and west - Harding, Vanessa; Watanabe, Kōichi, 1959- (Cambridge Scholars Publishing, 2015)
Between the sixteenth and the nineteenth centuries, in both Western Europe and East Asia, towns and cities helped to shape the individual consciousness, against the background of a more traditional society in which collective values remained strong. Towns were centres of stimulus, challenge, and opportunity for residents and visitors, and the identity of the town itself, its character and history, became a strong theme in the formation of the individual. Writing and the circulation of texts played an important part in this process. Towns created artefacts, rituals, and memories that embodied t.